Interleukin-1 Beta in Peripheral Blood Mononuclear Cell Lysates as a Longitudinal Biomarker of Response to Antidepressants: A Pilot Study - Ferentinos, Panagiotis; Maratou, Eirini; Antoniou, Anastasia; Serretti, Alessandro; Smyrnis, Nikolaos; Moutsatsou, Paraskevi (Frontiers in Psychiatry, 2021)
Interleukin-1 beta (IL1b) is primarily produced by monocytes in the periphery and the brain. Yet, IL1b protein levels have to date been investigated in Major Depressive Disorder (MDD) and antidepressant response using either plasma or serum assays albeit with contradictory results, while mononuclear cell assays are lacking despite their extensive use in other contexts. In this pilot study, we comparatively assessed IL1b in mononuclear lysates and plasma in depressed MDD patients over treatment and healthy controls (HC). We recruited 31 consecutive adult MDD inpatients and 25 HC matched on age, sex, and BMI. Twenty-six patients completed an 8-week follow-up under treatment. IL1b was measured in both lysates and plasma in patients at baseline (T0) and at study end (T1) as well as in HC. We calculated ΔIL1b(%) for both lysates and plasma as IL1b percent changes from T0 to T1. Seventeen patients (65.4% of completers) were responders at T1 and had lower baseline BMI than non-responders (p=0.029). Baseline IL1b from either plasma or lysates could not efficiently discriminate between depressed patients and HC, or between responders and non-responders. However, the two response groups displayed contrasting IL1b trajectories in lysates but not in plasma assays (response group by time interactions, p=0.005 and 0.96, respectively). ΔIL1b(%) in lysates predicted response (p=0.025, AUC=0.81; accuracy=84.6%) outperforming ΔIL1b(%) in plasma (p=0.77, AUC=0.52) and was robust to adjusting for BMI. Concludingly, ΔIL1b(%) in mononuclear lysates may be a longitudinal biomarker of antidepressant response, potentially helpful in avoiding untimely switching of antidepressants, thereby warranting further investigation.